The place of estramustine phosphate in the management of prostate cancer [Prostat kanseri tedavisinde estramustin fosfatin yeri] - (:unkn) unknown (My University, 2003)
Estramustine phosphate has been extensively used in the management of prostate cancer with distinct purposes that include primary treatment of metastatic prostate cancer and adjuvant or neoadjuvant applications in the localised cases. However, the most common clinical use is in the management of hormone refractory prostate cancer. Oral administration provides an important preference and also proven synergism with a number of chemotherapetic agents has caused utilisation in different combinations. The PSA response was documented between 30 to %60 in these studies. Gastrointestinal tract and cardiovascular toxicities are the main drawbacks. In conclusion, estramustine phosphate with respect to its easy administration as a hormonal and chemotherapeutic agent is one of the most common drugs used in the management of prostate cancer particularly in the case of hormone refractory disease.
Keywords: Estramustine phosphate; Prostate cancer